STRATEGI MANAJEMEN RISIKO PADA BISNIS PERJALANAN DI MASA PANDEMI COVID-19 - I Putu Esa Widahartana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Risks in the travel business company has been widely identified at this time to the pandemic requires attention and priority handling to overcome huge losses experienced by different companies. Risk management is one of the important elements in running the company's business, especially in the field of travel business because of the growing world of the company, the increasingly fierce competition, and the increasing complexity of company activities resulting in the increasing level of risk faced by the company. The purpose of writing this article is to explain the concept of risk management and risk management in a company or organization. The writing method is based on literature review. This research uses qualitative research methods through netnographic data, namely analysis to explore a phenomenon in a group. Qualitative analysis techniques to be able to determine the right results and strategies regarding the handling of Covid-19 in Indonesia, especially in the field of travel. The findings of this study provide recommendations for implementing a nature-based rural tourism model that minimizes the scope of the crowd but still looks attractive with various packaging activities carried out by tourism actors in the village.